Wine tourism experience vis-à-vis wine tourism development: A netnographic analysis of namibian wineries - Elsie Vezemburuka Hindjou; Saurabh Kumar DIXIT (Tourism and Hospitality Management)
Purpose – The overriding objective of this study is to analyse the visitors’ experience via online reviews vis-a-vis the wine tourism development in Namibia. Therefore, the study identified critical elements influencing visitor experiences and their perceived destination image. Methodology/Design/Approach – This study adopted netnography as non-participant observation and is based on online reviews published on TripAdvisor (www.TripAdvisor. com) between 2013/2023. The study analysed the reviews to identify critical elements that the visitors highlighted as influencing their experiences and their perceived destination image. In the next step of data processing, NVivo 12.6.1 (3859) was used to identify themes/elements and determine the extent to which each factor influencing visitors’ experiences at wineries was referenced. A relationship mapping was conducted using IBM SPSS Statistics 29.0.2.0 to study the relationship between satisfaction/dissatisfaction and post-consumption behaviour (revisit intention & recommendation). Findings – The study analysed the reviews to identify critical elements that the visitors highlighted as influencing their experiences and their perceived destination image. The final list comprises ten elements/themes: hospitality, wine quality and pricing, wine-related activities, service quality, ambience, family-friendly, food quality, and other facilities and activities. The relationship between satisfaction and recommendation was found to be not just significant, but a key factor in influencing visitor experiences and their perceived destination image. Originality of the research – The paper aims to analyse wine tourism experience vis-à-vis wine tourism development. It underscores that wine tourism-related visitors’ satisfaction, resulting from excellent experiences, can be presented as a compelling argument for developing a truly exclusive Namibian wine tourism experience. Despite not being perceived as a prominent wine destination, Namibia has the potential to transform into a genuinely unique and exclusive wine tourism destination with the collaboration of key stakeholders, a potential this research brings to light.